Performance-Based Finite Element Investigation of Concrete-Filled Steel and FRP Tubular Columns under Axial Compression - Magar, Anish Thapa; Kandel, Sayana; Shrestha, Suyogya; Shah, Sneha; Thakur, Rohini (Journal of Advanced College of Engineering and Management, 2026)
Reinforced concrete columns are prone to brittle failure under larger axial and seismic loads, highlighting the need for improved structural systems. Although concrete-filled steel tube (CFST) and concrete-filled FRP tube (CFFT) columns offer enhanced performance due to confinement effects, limited studies provide a direct comparison within a unified framework. This paper presents a comparative evaluation of CFST and CFFT columns using finite element modelling in Abaqus, based on confined concrete damage plasticity model for infilled concrete, a plasticity model for steel tubes, and the Hashin damage model for FRP tubes, with validation against experimental results available in the literature. A parametric study was conducted by varying tube thickness, rebar diameter, tube cross-sectional shape, and slenderness ratio. The results showed that increasing the tube thickness from 2 mm to 8 mm enhanced the peak strength of CFST and CFFT columns by 69.54% and 55.6%, respectively, while increasing the rebar diameter from no reinforcement to 16 mm improved the peak strength by 45.6% and 58.36%, respectively. Columns with circular sections exhibited superior performance due to uniform confinement, whereas non-circular sections showed reduced strength. Increasing the slenderness ratio reduced load-bearing capacity and flexural stiffness, thereby increasing buckling susceptibility. Overall, CFST columns exhibited higher strength and stiffness, whereas CFFT columns showed greater ductility because the FRP tube provides effective lateral confinement, allowing greater expansion of the concrete core before rupture. However, due to the relatively low elastic modulus of FRP, its contribution to axial stiffness remains limited.